1977
DOI: 10.1159/000180897
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Some Clinical and Histological Parameters in Membranoproliferative Glomerulonephritis (MPGN)

Abstract: 112 cases of MPGN, whose diagnosis was made on light microscopy, were reviewed. Histological examination showed 66 cases of ‘classical’ MPGN, 33 of MPGN with a lobular pattern and 13 of MPGN with epithelial crescents. In 11 patients dense intramembranous deposits were observed. On immunofluorescence (95 cases) 62 patients showed deposits of C3 together with immunoglobulins, 20 had a predominant deposition of C3 and in 13 C3 alone was present. At the moment of biopsy 57 patients had nephrotic syndrome, 43 hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1

Year Published

1979
1979
2005
2005

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 9 publications
2
6
1
Order By: Relevance
“…Our results are in agreement with those of other authors who have reported similar survival rates with smaller numbers of cases [1-3, 5-10, 12, 13, 16], mostly including many children as well as cases with MPGN type II [1][2][3][5][6][7][8][9]12]. Only Barbiano di Belgiojoso et al [4] got more favorable results with a 70% probability of maintaining renal function after 10 years. In contrast, in the studies published by Kincaid-Smith [10] and Mandelanakis et al…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results are in agreement with those of other authors who have reported similar survival rates with smaller numbers of cases [1-3, 5-10, 12, 13, 16], mostly including many children as well as cases with MPGN type II [1][2][3][5][6][7][8][9]12]. Only Barbiano di Belgiojoso et al [4] got more favorable results with a 70% probability of maintaining renal function after 10 years. In contrast, in the studies published by Kincaid-Smith [10] and Mandelanakis et al…”
Section: Discussionsupporting
confidence: 92%
“…The fact that glomerular lesions are not significant for the course of the disease is also shown by earlier studies [1,7,8]: only Barbiano di Belgiojoso et al [4] found a poorer prognosis for lobular glomerulonephritis which corresponds to our grade IV. Even though we observed an unfavorable influence of focal crescent formation (grade V) on the course of MPGN -as other authors before us [1,2,4,7,8,10], we still do not believe that the crescents cause the progression of the disease; rather we suspect that in these cases the almost obligatorily present tubulointerstitial lesions determine the outcome [19]. Among clinical parameters hypertension and an elevated serum creatinine concentration at the time of biopsy are of prognostic significance.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The more probable outcome is chronic deterioration of renal function leading to ESRD in approximately half of patients within 10 yr of diagnosis (22)(23)(24)(25). In some patients, rapid fluctuations in proteinuria occur with episodes of acute renal deterioration in the absence of obvious triggering events; in others, the disease remains stable for years despite persistent proteinuria.…”
Section: Clinical Diagnosismentioning
confidence: 99%
“…C3NeF is nearly always associated with clinical evidence of complement activation such as a reduction in CH50, a decrease in C3, and an increase in C3dg/C3d; however, the relationship among C3NeF, C3 levels, and prognosis is unclear. Some groups report no correlation between C3 levels and clinical course (18,24,26,27), whereas other groups have found persistent hypocomplementemia indicative of a poor prognosis (28,29).…”
Section: Clinical Diagnosismentioning
confidence: 99%